Identifying Skill Requirements for GIS Positions: A Content Analysis of Job Advertisements. Issue 4 (3rd July 2016) - Hong, Jung Eun
Abstract : This study identifies the skill requirements for geographic information system (GIS) positions, including GIS analysts, programmers/developers/engineers, specialists, and technicians, through a content analysis of 946 GIS job advertisements from 2007–2014. The results indicated that GIS job applicants need to possess high levels of GIS analysis and modeling skills (e.g., database development) and personal and social skills (e.g., communication) to obtain employment, although specific skill requirements differed significantly depending on job title. The findings from this study may be useful for improving GIS majors' employability.